Hidroretentor como alternativa para a produção de Tagetes patula L. sob irrigação salobra - Sousa, Naara Iorrana Gomes (2022)
The general objective of this research was to evaluate the effect of the hydrogel in minimizing damage caused by salinity in the production of marigold (Tagetes Patula L.). The research was carried out in a greenhouse, in the experimental area of the agromeorological station, belonging to the Federal University of Ceará (UFC), Fortaleza, Brazil. The work was divided into 2 chapters corresponding to the two phases of the experiment. The first phase took place in September 2020, in a randomized block design in subdivided plots, where the plots corresponded to seven electrical conductivities of the irrigation water CEa (0.5; 1.0; 2.0; 3.0; 4.0 ; 5.0 and 6.0 dS m-1) and the subplots corresponded to four hydrogel concentrations (0.0; 1.0; 2.0 and 3.0 g L-1 ), with 5 repetitions and each subplot was composed of 27 seeds. The analysis of emergence variables and number of live seedlings showed that the increase in salinity reduced the germination percentage, promoting seedling death, regardless of the hydrogel dose. The use of 3 g of hydrogel per liter of substrate favored the production of leaves and reduced the heat stress associated with the increase in salinity of the substrate, promoted an increase in seedling height, leaf dry mass and total dry mass in relation to treatments without the polymer, even at moderate (2.0 to 3.0 dS m-1) and high (4.0 to 6.0 dS m-1) salinity levels of the irrigation water, indicating a possible effect of mitigating the damage caused by salinity. The second phase of the research was carried out between December 2020 and February 2021, using a randomized block design with split plots, where the plots corresponded to the seven electrical conductivities of the irrigation water (0.5; 1.0; 2.0 ; 3.0; 4.0; 5.0; 6.0 dS m-1) and the subplots correspond to two hydrogel concentrations (0.0 and 3.0 g L-1), with 5 repetitions. The use of 3.0 g L-1 of hydrogel showed an improvement in the availability of water for the plants, mitigating the water stress caused by the osmotic effect and increasing the production of leaves and flowers regardless of salinity. The use of 3.0 g L-1 increased seedling quality and provided favorable conditions for morphological adjustment. The species Tagetes patula L. was accepted by consumers especially up to ECa 3.0 dS m-1 and was classified as moderately tolerant by the Ornamental index method. Regardless of the hydrogel concentration, the increase in salinity reduced the percentage of emergence, however the use of 3.0 g L-1 of hydrogel reduced the heat stress of the seedlings and increased seedling quality, water use efficiency and resistance to salinity.